OPTIMALISASI PRECOATING ASAM JERUK NIPIS PADA BAJA TERHADAP KEKASARAN PERMUKAAN - Listiyono Listiyono (Universitas Lambung Mangkurat, 2017)
The process of coating is a metal coating process well with other metals or metal oxides. Even now coating paint / color is also using coating processes. Therefore, there is a hot coating, powder coating, electrical coating, and so forth. Therefore it is necessary to examine more deeply how to get the high-quality coating process. The type of coating used herein are electrically degreasing. A metal plating actors not only get results pengalanman other people are there in the field. The problem until now no one has conducted a study / research in the coating process (electrically degreasing) metal with acids of fruits .Penelitian was conducted in the Laboratory of Mechanical Engineering Polteknik Malang The aim of this study are: 1. Finding how much influence sour lime in steel metal precoating process. 2. Determining factors and optimum levels to get to the surface roughness of steel precoating results.The method used in this research was Factorial Design of Experiments. By taking two factors: the solution concentration and flow of electrically degreasing processes (coating) and. There are 3 levels of concentration are: 5 ml / liter, 10 ml / liter, and 15ml / liter of water. level. While the current level of 3 amps, 4 amp and 5 amp. With experimental data collection techniques. Analysis with MINITAB.The results in the interaction factor concentration and electrical currents can affect the outcome of citric acid degreasing. Concentration and optimal flow in precoating process citrate was 5 ml / l and 5 amperes.